2021
DOI: 10.4236/psych.2021.128073
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Political Conservatism as Predictors of Blaming Asian Victims of Hate Crimes in the U.S. during the COVID-19 Pandemic

Abstract: The purpose of this study was to investigate the potential impact of U.S. government official's comments regarding the source of COVID-19 on individuals' perceptions and tendencies to blame Asian victims of hate crimes in the U.S. Moreover, we examined how political conservatism and beliefs about the origin and spreading of COVID-19 impact participants' victim blaming toward Asian victims of hate crimes. Participants (N = 100; 46 women, 54 men) were recruited via Amazon's Mechanical Turk (MTurk). Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…From the abovementioned findings, it is reasonable to suggest that with the ongoing COVID-19 threat, more people are showing preference for a more conservative view toward society, and this in turn makes them more likely to have negative attitudes toward outgroup members in the U.S.-Asian Americans. Higher RWA is also associated with higher victim blaming attitudes during COVID-19 (Yamawaki et al, 2021). This indicates that covert acts of prejudice already exist in the context of this pandemic, and it also provides reasons for overt or more serious acts of hostility to occur when the consequences of such actions are being ignored.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…From the abovementioned findings, it is reasonable to suggest that with the ongoing COVID-19 threat, more people are showing preference for a more conservative view toward society, and this in turn makes them more likely to have negative attitudes toward outgroup members in the U.S.-Asian Americans. Higher RWA is also associated with higher victim blaming attitudes during COVID-19 (Yamawaki et al, 2021). This indicates that covert acts of prejudice already exist in the context of this pandemic, and it also provides reasons for overt or more serious acts of hostility to occur when the consequences of such actions are being ignored.…”
Section: Discussionmentioning
confidence: 87%
“…We utilized 10 real-world scenarios of Asian Americans experiencing aggression due to the COVID-19 pandemic. These scenarios were previously utilized by Yamawaki et al (2021). Example scenarios included the following:…”
Section: Scenariosmentioning
confidence: 99%
“…Sebagaimana dikonsepsikan oleh Mason (2015), rasialisme semakin meningkat ketika mengasosiasikan penyakit dengan kondisi geografis wilayah tertentu. Tanpa diduga, dunia membuktikan sejak awal 2020 seperti yang dicatat Gardner et al (2022) dan Yamawaki et al (2021) yang menguraikan diskriminasi ras meningkat sepanjang pandemi. Banyak orang menyalahkan dan meyakini bahwa orang Asia menjadi pelaku penyebaran virus ke Amerika.…”
Section: [Ega Riadiska Dan Sumekar Tanjung] [Penerimaan Komunitas Mon...unclassified
“…Despite these claims, past research has shown that conservatives tend to express more prejudice towards ethnic groups than liberals (e.g., Prezza et al, 2008 ). In addition, during the pandemic, politically conservative individuals were more likely to dehumanize Asian Americans ( Markowitz et al, 2021 ) and to blame them for being victims of hate crimes ( Yamawaki et al, 2021 ). Thus, conservative-leaning individuals may be more inclined to display prejudice and discrimination, particularly when interacting with Asian Americans high in Chinese phenotypicality.…”
Section: The Relation Between Individual Difference Characteristics A...mentioning
confidence: 99%